Luminol-amplified chemiluminescence: a sensitive method for detecting the carrier state in chronic granulomatous disease. - Mills, E L (1980)
Patients with chronic granulomatous disease have a marked defect in neutrophil oxidative metabolism and microbicidal activity. Asymptomatic mothers of males with the disease can usually be identified as heterozygous carriers by intermediate leukocyte function. Most mothers of females with the disease, however, have normal leukocyte function, and the pattern of genetic transmission in these families has been difficult to establish. Of 14 mothers of males and females with chronic granulomatous disease, 10 had been found previously to have intermediate values for neutrophil bactericidal activity, oxygen consumption, hexose monophosphate shunt activity, and Nitro Blue Tetrazolium reduction, and 4 had normal in viro leukocyte function. In the present study, 4 of these 14 mothers had normal neutrophil bactericidal activity, 3 had normal zymosan-stimulated chemiluminescence, but none had normal luminol-amplified zymosan-stimulated chemiluminescence. The presence of luminol (5-amino-2,3-dehydro-1,4-phthalazinedione) in the phagocytic mixtures markedly increased the sensitivity of the assay, permitting detection of subtle defects in leukocyte oxidative metabolism in three previously unidentifiable carriers of the disease. Thus, luminol-amplified chemiluminescence appears to be one of the most sensitive methods available for detection of chronic granulomatous disease heterozygotes; the simplicity and reproducibility of the microtechnique permit evaluation of leukocyte function in infants and newborns.